Effects of noninvasive brain stimulation on dual-task performance in different populations: A systematic review - Lin, Xiaoying; Zhang, Yanming; Chen, Xi; Wen, Lifen; Duan, Lian; Yang, Lei (Frontiers in Neuroscience, 2023)
Background Increasing research has investigated the use of noninvasive brain stimulation (NIBS) on augmenting dual-task (DT) performance. Objective To investigate the effects of NIBS on DT performance in different populations. Methods Extensive electronic database search (from inception to November 20, 2022) was conducted in PubMed, Medline, Cochrane Library, Web of Science and CINAHL to identify randomized controlled trials (RCTs) that investigated the effects of NIBS on DT performance. Main outcomes were balance/mobility and cognitive function under both single-task (ST) and DT conditions. Results Fifteen RCTs were included, involving two types of intervention techniques: transcranial direct current stimulation (tDCS) (twelve RCTs) and repetitive transcranial magnetic stimulation (rTMS) (three RCTs); and four different population groups: healthy young adults, older adults, Parkinson’s disease (PD), and stroke. For tDCS, under DT condition, significant improvement in speed was only observed in one PD and one stroke RCT, and stride time variability in one older adults RCT. Reduction in DTC in some gait parameters was demonstrated in one RCT. Only one RCT showed significant reduction in postural sway speed and area during standing under DT condition in young adults. For rTMS, significant improvements in fastest walking speed and time taken to Timed-up-and-go test under both ST and DT conditions were observed at follow-up in one PD RCT only. No significant effect on cognitive function in any RCT was observed. Conclusion Both tDCS and rTMS showed promising effects in improving DT walking and balance performance in different populations, however, due to the large heterogeneity of included studies and insufficient data, any firm conclusion cannot be drawn at present.